Examining spiritual concepts in health services - Fatemi-Amin, Nasrolah; Talebi, Mohsen (Researcher Bulletin of Medical Sciences, 2026)
Objective: Health has different dimensions. One of the most important dimensions of health is its mental and spiritual aspect, which has recently received the attention of researchers. Spirituality is considered one of the important aspects of human life. In today’s civilized world, paying too much attention to the material aspects of human life has caused the spiritual dimension of human life to be forgotten. Materials and Methods: One of the important areas in which this dimension of human life is manifested is the time when a person is suffering from illness and goes to health and treatment centers. Man’s confrontation with illness makes the soul aware of the mortality of material life and is a push to pay more attention to spirituality and immaterial dimensions; However, in healthcare centers, this issue has not been paid much attention and is often ignored. Results: Although various studies have confirmed the usefulness of using religious and spiritual beliefs in patient care, most people involved in patient care refrain from doing so. This is while giving importance to the spiritual dimension during illness and illness, especially in centers that deal with human health, causes the pain and suffering of patients to subside and raise their level of health; In addition, spiritual attention also plays an important role in the awareness of the human soul and provides a suitable ground for getting close to God and human evolution. Conclusion: Therefore, this study was carried out with the aim of explaining the concept of spirituality in the field of healthcare services and investigating various solutions for its application in this field, so that the necessary recommendations and training can be provided to people related to healthcare professions.